2015
DOI: 10.1039/c5ta01739d
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of zinc cobalt sulfide nanostructures in oil phase and their potential applications in electrochemical energy storage

Abstract: A unique controlled synthesis of zinc cobalt sulfide nanostructures is obtained by a facile oil phase approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(70 citation statements)
references
References 55 publications
2
67
1
Order By: Relevance
“…[43,44] FeCo 2 S 4 is similar to NiCo 2 S 4 as electrode material, thus it is believed that its energy storage mechanism in alkaline electrolyte should be via a reversible redox reaction of FeCo 2 S 4 to form FeSOH, CoSOH, and CoSO. The C g values for the optimal FeCo 2 S 4 electrode are all roughly double those of the FeCo 2 O 4 electrode, and also higher than other ternary transition metal sulfides nanostructures such as CuCo 2 S 4 nanosheets, [45] Zn x Co 1−x S nanoartichokes, [15] MnCo 2 S 4 nanotubes, [27] and NiCo 2 S 4 with different morphologies [16,17,[46][47][48] (see Table S1, Supporting Information). The C g values for the optimal FeCo 2 S 4 electrode are all roughly double those of the FeCo 2 O 4 electrode, and also higher than other ternary transition metal sulfides nanostructures such as CuCo 2 S 4 nanosheets, [45] Zn x Co 1−x S nanoartichokes, [15] MnCo 2 S 4 nanotubes, [27] and NiCo 2 S 4 with different morphologies [16,17,[46][47][48] (see Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…[43,44] FeCo 2 S 4 is similar to NiCo 2 S 4 as electrode material, thus it is believed that its energy storage mechanism in alkaline electrolyte should be via a reversible redox reaction of FeCo 2 S 4 to form FeSOH, CoSOH, and CoSO. The C g values for the optimal FeCo 2 S 4 electrode are all roughly double those of the FeCo 2 O 4 electrode, and also higher than other ternary transition metal sulfides nanostructures such as CuCo 2 S 4 nanosheets, [45] Zn x Co 1−x S nanoartichokes, [15] MnCo 2 S 4 nanotubes, [27] and NiCo 2 S 4 with different morphologies [16,17,[46][47][48] (see Table S1, Supporting Information). The C g values for the optimal FeCo 2 S 4 electrode are all roughly double those of the FeCo 2 O 4 electrode, and also higher than other ternary transition metal sulfides nanostructures such as CuCo 2 S 4 nanosheets, [45] Zn x Co 1−x S nanoartichokes, [15] MnCo 2 S 4 nanotubes, [27] and NiCo 2 S 4 with different morphologies [16,17,[46][47][48] (see Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 95%
“…On one hand, in order to gain the desirable nanostructures, a relatively low C S 2− is necessary for sulfidation etching from surface to the interior, but only surface sulfidation happens instead if the C S 2− is too low. [11][12][13][14][15][16] The rough surface is due to the presence of many nanosheets that interconnect with each other leading to a uniformly porous nanostructure (insets of Figure 2b and Figure S1b, Supporting Information). On the other hand, at the relatively slow anion-exchange rate (C S 2− = 10 × 10 −3 m), a long enough t R is important for a complete composition conversion.…”
Section: Resultsmentioning
confidence: 99%
“…[20] For example, Dong et al synthesized urchinlike Zn 0.76 Co 0.24 S, which showed as pecific capacitance of 486.2 Fg À1 at 2Ag À1 and a capacitance retention of 86.4 %f or 2000 cycles. [21] Lou et al preparedc ore-shell Zn-Co-S with ac apacitance of 1266 Fg À1 at 1Ag À1 ,a nd 91 %o ft he initial capacitancew as maintained after 10 000 cycles. [22] However,p oor transfer efficiency of electrons and ions of ZCS for supercapacitors hinders its electrochemical response.…”
Section: Introductionmentioning
confidence: 99%
“…As ac onsequence, the electrochemical performances could be remarkably enhanced for applications in LIBs. [16][17][18] Many BMS materials,s uch as NiCo 2 S 4 , [19] Cu 2 SnS 3 , [20] CoSnS 4 , [21] MnCo 2 S 4 , [22] and Zn 0.76 Co 0.24 S, [23] have been investigated as anode materials for LIBs. For example, Yang et al designed 3D Zn 0.76 Co 0.24 Sn anoartichokes as anode material for LIBs, which exhibited ah igh capacity of 750 mA hg À1 at ac urrent density of 200 mA g À1 after 100 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yang et al designed 3D Zn 0.76 Co 0.24 Sn anoartichokes as anode material for LIBs, which exhibited ah igh capacity of 750 mA hg À1 at ac urrent density of 200 mA g À1 after 100 cycles. [23] Jin et al synthesized 3D urchinlike NiCo 2 S 4 hollow microspheres, which showed as pecific capacity of 411mAhg À1 at ah igh current rate of 2Ag À1 .T he reactionm echanism of NiCo 2 S 4 and Li + can be depicted as follows:N iCo 2 S 4 + 8Li + + 8eÀ!Ni + 2Co + 4Li 2 S and Ni + Li 2 S$NiS + 2Li and Co + Li 2 S$CoS + 2Li. Both the capacity and rate capability are superior to those of pure NiS or CoS. [19] More recently,v arious CuCo 2 S 4 nanomaterials (e.g., nanoarrays, [24] nanosheets, [25] and hollow spheres [26] )h ave drawn much attention because of their lower resistivity (approximately 10 À4 W)a nd stable structure.…”
Section: Introductionmentioning
confidence: 99%